Ozone fumigation effects on bacterial and anthracnose development on bell pepper (Capsicum annuum L.) and its effect on fruit quality - Alwi, Nurul Alyaa (2017)
Bacterial contamination and anthracnose development on bell pepper pose a threat to food safety and food security. Bacteria contamination by pathogenic species can be a fatal outbreak and risking worldwide population. Meanwhile, anthracnose development on bell pepper can contribute to substantial product loses which will substantially affect world economy and food availability. Current postharvest treatment such as the use of chlorine and fungicide poses harmful effects on human and environment due to the production of carcinogenic by-products. This leads to urgency to develop a safe postharvest treatment which leads to the objective of this study to develop a new postharvest treatment; ozone fumigation which has high potential to reduce bacterial contamination and anthracnose development on bell pepper. Ozone fumigation treatment is safe to human and environment and very practical. This technology is promising hence, worth to study.